Occurrence of Salmonella spp. In Water of recreational park in Kuching area - Nuramirah, Binti Ahmad Nadzari (Universiti Malaysia Sarawak (UNIMAS), 2013)
Salmonella spp. is a pathogenic bacterium that is widely distributed in environment. Salmonella cause a broad range of infections, including gastroenteritis, enteric fever, bacteremia, endovascular infections, osteomyelitis and abscesses. Salmonella is most commonly transmitted through contaminated food or water. This study was conducted to detect the presence of Salmonella typhimurium and S. enteritidis together with the analysis of water quality at recreational water; Unimas lake and Ranchan Waterfall Park. Total coliform using MPN method is used as a level of indicator to detect the presence of coliform bacteria. Identification of Salmonella spp. that includes culture methods based on selective media followed by identification methods involving phenotypic characterization through gram staining. Multiplex PCR was used to detect the Salmonella tyhimurium and S. enteritidis with the used of primers Sef t67 and Sef 478 and Tym and Fli 15. The correlation between the occurence of Salmonella spp. with the physiochemical parameter (temperature and pH) also being studies. Thirteen Salmonella enteritidis were isolated in the course of the study that targeting the 312 bp of sefA gene and none of S. typhimurium was isolated that targeting 559 bp ofjliC gene.